The Analysis of Profession of Insolvency Trustee - Hlaváčková, Kateřina; Pauknerová, Daniela, 1970-; Půbalová, Kateřina; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2017)
This master’s thesis provides a comprehensive overview of the profession of an insolvency trustee in the Czech Republic and of Czech insolvency trustees, as professionals. None of these areas has been examined and described before. This thesis is divided in two parts. The first is theoretical and describes the scientific approach of job analysis as well as legal regulation of the insolvency trustees in the Czech Republic. The second, practical part then contains the analysis of the profession in the form of an professiogram and analysis of the professionals in the form of a profile of typical trustee. The analyses are based on extensive primary research, during which all reachable insolvency trustees in the Czech Republic were addressed, as well as on primary data from public sources.
Vedoucí práce: Daniela Pauknerová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses